Online Analysis of Reputation Management PT. Infodood About Indomie Has No Seasoning - Annisa Yahya, Shaila; Maulida, Ade; Anggriani, Dhea (Educationist: Journal of Educational and Cultural Studies, 2023)
Indomie which did not have seasoning on the package make Edwin Achmad, as a noodle consumer, complain about this through Indomie's official Instagram. Which had verified its existence. After that, he shared his grievances on a Facebook forum, namely the Instant Noodle World, unexpectedly that his viewers soared so high that they went viral and attracted the attention of many public. Online news on social media, Tiktok, began to publish this matter, so that many netizens voiced the same opinion on several blogs, review sites, and Twitter. Pros and cons among netizens occurred in response to this incident. The reputation that has been built for so long by PT. Indofood was almost threatened, because this incident happened not only once or twice, but often. Mie Sedap as a competitor sees it as an opportunity to be one step ahead in terms of tidiness of packaging, but fortunately, Indomie is responsive to maintaining its company's reputation by being ready to serve 24 hours various consumer complaints and will respond within a maximum period of 2 X 24 hours and Re-shipping new products as a form of compensation, this is a form of online reputation management efforts by Indomie. And to add a positive impression and support from the community, PT. Indofood publishes CSR in the form of the Indofood Sukses Makmur Scholarship (BISMA), a scholarship intended for the children of outstanding employees.